The Effect of Counseling on Contraceptive Selection in Women of Reproductive Age Couples - Podungge Yusni; Igirisa Yusni (Science Midwifery, 2021)
One of the efforts made by the government to control the rate of population growth is through the Family Planning Program (KB). Puskesmas Sipatana is one of the areas in Gorontalo City with a high number of live births 17.36% and 17.66% low active birth control. The low coverage of family planning services is a challenge in midwifery services, for that socialization is more intensified by using digital channels, such as electronic media so that it can still reach the wider community. The research objective was to analyze the effect of counseling on contrast selection among women of childbearing age in the working area of ​​Puskesmas Sipatana, Gorontalo City. The experimental design used in this study was a pre-experimental design with a One-group posttest only design approach. The variables in this study consisted of independent variables, namely counseling and dependent variables in the choice of contraceptive methods. The study population was all women in the appropriate age of 1400 and the sample that met the inclusion criteria was 100 respondents. The research was conducted from September to December 2020. The results of the linear regression test showed that education, work, knowledge and attitudes had no effect on contraceptive choice. Age, parity and counseling influence the choice of contraception. The multivariate test results show that age is the dominant variable that influences the choice of contraception.